2000
DOI: 10.1176/appi.ajp.157.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Recurrences of Major Depressive Disorder

Abstract: Major depressive disorder is a highly recurrent illness. The risk of the recurrence of major depressive disorder progressively increases with each successive episode and decreases as the duration of recovery increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
441
2
16

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 690 publications
(498 citation statements)
references
References 19 publications
14
441
2
16
Order By: Relevance
“…1 Without treatment, depression has the tendency to assume a chronic course, be recurrent, and over time to be associated with increasing disability. 4,5 The comorbidity of depression with chronic physical diseases such as arthritis and diabetes is well recognised in developed countries. [6][7][8][9] Several studies have shown that there is an increased risk of having major depression in people with one or more chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…1 Without treatment, depression has the tendency to assume a chronic course, be recurrent, and over time to be associated with increasing disability. 4,5 The comorbidity of depression with chronic physical diseases such as arthritis and diabetes is well recognised in developed countries. [6][7][8][9] Several studies have shown that there is an increased risk of having major depression in people with one or more chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…MDD is a highly recurrent disorder and risk of recurrence is related to the number of previous episodes (Solomon et al 2000;Kessing et al 2004). This observation stimulated the idea that depressive episodes leave more or less permanent residual impairments or scars that confer risk of subsequent episodes; the 'scar hypothesis' (Rohde et al 1990;Burcusa & Iacono, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment options (psychological, pharmacological, and neurostimulation interventions) are moderately successful in achieving initial symptom reduction but long-term effects are less encouraging, with research showing that recurrence of MDD (i.e., experiencing a depressive episode after having exhibited full and/or partial remission from a previous depressive episode) is high in Cognitive Emotion Regulation Questionnaire (CERQ; Garnefski et al, 2001) was used to assess a broad range of emotion regulation strategies, which allows calculation of compound scores for (3) adaptive and (4) maladaptive emotion regulation processes. (5) The Remission from Depression Questionnaire (RDQ; Zimmerman et al, 2013) was used as an indicator of residual symptoms following (partial) remission from depression given that previous work indicates that residual symptomatology increases the chance of recurrence of depressive episodes (e.g., Solomon et al, 2000). This questionnaire provides a more nuanced assessment of remission than standard measures of depressive symptomatology as it combines assessment of residual depressive-and related symptoms with indicators of functioning such as sense of well-being.…”
Section: Introductionmentioning
confidence: 99%